Effects of dietary organic selenium on immune responses, total selenium accumulation and digestive system health of marron, Cherax cainii (Austin, 2002) - Nugroho, Rudy; Fotedar, Ravi (Wiley-Blackwell Publishing Ltd., 2013)
A 90-day feeding trial was conducted to determine the effects of dietary organic selenium (OS) supplementation on immune responses, total selenium accumulation in various tissues and the digestive system health of marron Cherax cainii. A group of marron (initial weight 3.65 ± 0.05 g) were fed 0.2 g kg -1 of Sel-Plex as a source of OS and were compared to a control group of marron that were not fed OS. After 90 days of feeding OS, total haemocyte counts (THC) and the percentages of granular and semigranular cells in marron were significantly higher than in marron fed a control diet. However, dietary OS did not affect the proportion of hyaline cells. The marron fed OS had significantly lower bacteraemia and longer neutral red retention times than the control group. Total selenium levels in the haemolymph, hepatopancreas and muscle tissues of the OS-fed marron group were significantly higher (P < 0.05) than in control diet group. The highest total soluble selenium levels were found in the muscle tissues of OS-fed marron on the final day of the feeding trial. Amylase and protease activity, soluble protein, and numbers of microvilli were significantly higher (P < 0.05) in marron fed OS. These findings demonstrate the benefits of including 0.2 g kg-1 OS in marron diet to enhance immune parameters, increase total selenium accumulation in muscle and improve marron digestive system health.